The Problems and Prospects of the Nonstate Financing of Socio-Economic Development - Holovnia Olena M. (Bìznes Inform, 2018)
The article is aimed at evaluating the possibilities of nonstate financing of social development with use of new methods. The leading place among them belongs to public organizations and progressive mechanisms of fundraising. Responding to the need for innovative technologies to manage social development, the national economy should launch mechanisms for revitalizing modernization processes. For this purpose it is necessary to generate new means of achievement of socio-economic goals, in particular intensive attraction of funds. To such innovative technologies belong fundraising, crowdfunding, and crowdsourcing. By performing a derivative role, such technologies are an efficient instrument for creating a platform of promoting the nonstate financing for social development. Contributers to innovative technologies are authors of original projects, startups, companies, organizations, sponsors, and consumers of original products. Financing social projects through grants is a significant step forward in terms of developing the social responsibility for business and participation in the Global Compact.